The mirror of health discovering medicine in the Golden Age of Islam - Pormann, Peter E. (Royal College of Physicians of London, 2013)
The mirror of health : discovering the Golden Age of Islam examines the Royal College of Physicians' collection of Arabic and Persian medical texts - which has never been on public display before. This catalogue accompanied the 2013 exhibition which explored the development of medical science in the Middle East and Europe, via the medical traditions that developed in the heartland of Islam from the 9th to the 17th century. This fascinating story is illustrated by the RCP's collection of Islamic manuscripts dating from the 1200s to the 1900s